The Personality Trait of Intolerance to Uncertainty Affects Behavior in a Novel Computer-Based Conditioned Place Preference Task - Radell, Milen L.; Myers, Catherine E.; Beck, Kevin D.; Moustafa, Ahmed A.; Allen, Michael Todd (Frontiers in Psychology, 2016)
Recent work has found that personality factors that confer vulnerability to addiction can also affect learning and economic decision making. One personality trait which has been implicated in vulnerability to addiction is intolerance to uncertainty (IU), i.e. a preference for familiar over unknown (possible better) options. In animals, the motivation to obtain drugs is often assessed through conditioned place preference (CPP), which compares preference for contexts where drug reward was previously received. It is an open question whether participants with high IU also show heightened preference for previously-rewarded contexts. To address this question, we developed a novel computer-based CPP task for humans in which participants guide an avatar through a paradigm in which one room contains frequent reward and one contains less frequent reward. Following exposure to both contexts, subjects are assessed for preference to enter the previously-rich and previously-poor room. Individuals with low IU showed little bias to enter the previously-rich room first, and instead entered both rooms at about the same rate. By contrast, those with high IU showed a strong bias to enter the previously-rich room first. This suggests an increased tendency to chase reward in the intolerant group, consistent with previously observed behavior in opioid-addicted individuals. Thus, high IU may represent a pre-existing cognitive bias that provides a mechanism to promote decision-making processes that increase vulnerability to addiction.